Dietary Patterns, Physical Activity, and Lifestyle in the Onset, Prevention, and Management of Noncommunicable Diseases - Grant, William B.; Lordan, Ronan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue includes 12 articles, consisting of original research, narrative reviews, systematic reviews, and an editorial regarding the roles of dietary and lifestyle factors in the prevention and mangement of noncommunicable diseases. Studies in this Special Issue cover a range of topics including dietary patterns and diseases risk and prevention, the association of lifestyle factors and disease risk, the role of vitamin D and solar radiation in health and pregnancy, and urbanization in modifying risk of adverse health outcomes for various noncommunicable diseases.